2010
DOI: 10.1083/jcb.201005082
|View full text |Cite
|
Sign up to set email alerts
|

The F-BAR domain of SRGP-1 facilitates cell–cell adhesion during C. elegans morphogenesis

Abstract: SRGP-1 activity leads to outward bending and projections of membranes at cell–cell junctions, promoting robust adhesion between cells during embryonic closure events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
80
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(89 citation statements)
references
References 45 publications
9
80
0
Order By: Relevance
“…Although the most characterized function of F-BAR proteins is their role in endocytosis, many F-BAR proteins including CIP4 have also been shown to play a role in filopodial and lamellipodial protrusion (Carlson et al, 2011;Guerrier et al, 2009;Lee et al, 2010;Saengsawang et al, 2012;Zaidel-Bar et al, 2010). In nonneuronal cells, CIP4 induces polymerization associated with actin comet tails, endocytosis, and tubulation through its interaction with Cdc42, N-WASP and dynamin (Hartig et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Although the most characterized function of F-BAR proteins is their role in endocytosis, many F-BAR proteins including CIP4 have also been shown to play a role in filopodial and lamellipodial protrusion (Carlson et al, 2011;Guerrier et al, 2009;Lee et al, 2010;Saengsawang et al, 2012;Zaidel-Bar et al, 2010). In nonneuronal cells, CIP4 induces polymerization associated with actin comet tails, endocytosis, and tubulation through its interaction with Cdc42, N-WASP and dynamin (Hartig et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The RhoGAP domain of srGAP1 has been shown to promote GTP hydrolysis of Cdc42 and RhoA, depending on the concentration of Slit1 (Wong et al, 2001), whereas the GAP domains of srGAP2 and srGAP3 are both specific for Rac1 (Guerrier et al, 2009;Soderling et al, 2002), and ArhGAP4 can act on both Cdc42 and Rac1 (Vogt et al, 2007). All four family members display spatially and temporally distinct patterns of expression in the central nervous system (Bacon et al, 2009;Foletta et al, 2002) and have been shown to regulate cell migration and neuronal morphology in mammalian cells (Guerrier et al, 2009;Soderling et al, 2002;Vogt et al, 2007;Wong et al, 2001;Yang et al, 2006), a function that seems evolutionary conserved in invertebrates (Zaidel-Bar et al, 2010). srGAP3 has been implicated in a severe form of mental retardation, the 3p2 syndrome, giving srGAP3 the alternate name of mental-disorder associated GAP protein (MEGAP) (Endris et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The only worm homolog of mammalian srGAPs, SRGP-1, contributes to membrane dynamics at nascent cell-cell contacts and the formation of new AJs during gastrulation. This localization to, and regulation of, new AJs occurs independently of the cadherin homolog, HMR-1 (Zaidel-Bar et al 2010). This raises the possibility that Slit-Robo signaling through mammalian srGAPs may contribute to AJ formation during embryogenesis in a cadherin-independent manner.…”
Section: Slit-robo Regulation Of Adherens Junctionsmentioning
confidence: 99%